SELEKSI INDUK KAMBING PERANAKAN ETAWA BERDASARKAN NILAI INDEKS PRODUKTIVITAS INDUK DI KECAMATAN METRO SELATAN KOTA METRO - Yudi Asmara; Sulastri .; Idalina Harris (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2013)
Parent Productivity Index (IPP) is a picture of the ability of a parent to care for and raise theirchildren until the age of weaning until they reach a certain weaning weight within one year.Research purposes to determine the value of the parent group IPP Etawa Cross breed goats (PE)and determine the five male parent with IPP best value in the South Metro District, City Metro,Lampung Province.Survey method used in this study with a case study in the District of South Metro, Metro City. Thedata used are secondary data taken from the records of 40 breeding goats that had given birthtwice. The experiment was conducted on 20 October to 25 November 2012. Parameters observedin this study were aged mother at delivery, birth spacing, the number of children per birth parentgroup, birth weight and weaning, weaning age, sex, type of birth, and type of maintenance goatgroup.The results showed that the average weaning weight declined from 21.00 ± 1.05 kg, range 9.2 ±0.40 months of birth, number of children per birth tailed 1.83 ± 0.26, and 50.58 ± IPP values 8.76.IPP goat with the best value in a row C2 61.16; F2 59.79; G3 59.70; E2 59.29; I4 59.29. Based onthe results of this study suggested the goat breeders in the South Metro District 5 to give priority tothe goat breeders and other goat mother with IPP score above the average (21 of 40 head or52.5%) to be maintained in order to grown in population and get rid of the parent-parent with alow IPP score (14 out of 40 head or 35%).